Aerodynamic Analysis of Hybrid Drone. Issue 1 (January 2021) - Krishnaraj, S; Senthil Kumar, R; Gokula Krishnan, A; Ganeshkumar, G; Mohan, M; Nirmal, M
Abstract: Drones are Unmanned Aerial Vehicles (UAV's) or Remotely Piloted Vehicles (RPV's) whose application ranges from photography to defence. There are two major classifications of drone, one, a fixed wing; and another, a quadcopter. A hybrid drone is a kind of drone which has a mix of features of the two kinds of drone. It has quad-rotors for Vertical Take-Off Landing (VTOL), and a fixed wing for cruise. Aerodynamic analysis for a hybrid drone is done using Computational Fluid Dynamics (CFD) as a tool. A virtual wind tunnel test is done by means of this analysis. It is done in order to examine the various technical edges of the hybrid drone over the rest of the types. Firstly, the main entity of the drone, the wing, of 3 different profiles(aero-foils), is analysed for better lift coefficient as it is the major contributor for the thrust during cruise (for 0 deg angle of attack). The velocity contours are viewed to interpret the aerodynamic advantage of each wing. Then the whole vehicle is analysed after inculcating the wing. The various aerodynamic parameters such as the lift force, lift coefficient, drag force and drag coefficient of the hybrid drone are determined from the analysis. A hybrid drone with optimum lift has been designed from the inference.